THE ANALYSIS OF FACTORS AFFECTING MANAGEMENT PROFIT WITH DEVIDEND PAYOUT RATIO AS MODERATING VARIABLES IN COMPANIES MANUFACTURING LISTED IN INDONESIA STOCK EXCHANGE - Ningsih, Sulistio (International Journal of Public Budgeting, Accounting and Finance, 2018)
This study aims to determine the effect of Institutional Leadership, Proportion of Independent Commissioners, Company Size, Leverage, Free Cash Flow, Profitability, and Cost of Capital on Earnings Management with dividend payout ratio as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2012 -2015.This type of research is associative causal research. The population in this study is 125 companies and a sample of 56 companies using proportional sampling method, with the number of observations as many as 224 observation units. The method of data analysis in this study is multiple linear regression and residual test. The results of the first simultaneous hypothesis testing showed that the independent variables Institutional Ownership, Proportion of Independent Commissioner Board, Company Size, Leverage, Free Cash Flow,Profitability, and Cost of Equity Capital take effect towards Profit Management.Partially only Company Size variables affect earnings management, while Institutional Ownership variables, Proportion of Independent Commissioner Board, Leverage, Free Cash Flow, Profitability and Cost of Equity Capital has no effect on Management Profit. Testing the second hypothesis shows that the Dividend Payout Ratio is not able to moderate the relationship between Institutional Ownership, Proportion of Independent Commissioners, Company Size, Leverage, Free Cash Flow, Profitability and Cost of Equity Capital with earnings management in manufacturing companies listed on the Indonesia Stock Exchange.